The influence of a large mining company on the strategic behavior of a small company located in the interior of Minas Gerais: A case study on the impacts on Occupational Health and Safety Management (Research, Society and Development, 2021)
This paper aims to investigate the influence of a large mining company on the management of Occupational Health and Safety (HSO) in a small outsourced company that provides road implement manufacturing services, maintenance and sanitation of various vehicles. For this, the case study methodology was used in order to analyze in depth such influence. The research was divided into three phases, with are data collection, analysis and presentation of results, and report writing. The results indicate that there was a great influence of the mining company on issues related to HSO management. This influence could be highlighted through internal changes in the outsourced company, mainly in relation to the increase in investments and expansion of the commitment to occupational health and safety. These changes were motivated by contractual requirements established between them, which go beyond simple concerns with current legal requirements in the country.